Zinc Oxide Nanostructure Synthesis on Si(100) by Vapor Phase Transport and the Effect of Antimony Doping on Photoelectric Properties, Morphology, and Structure. (2020) - Trad, Tarek; Blount, Parker; Romero, Zuleyma; Thompson, David
ABSTRACT: Zinc Oxide (ZnO) has been shown to exhibit semiconducting and piezoelectric dual properties. This has led to a large commercial demand on ZnO for optoelectronics that operate at the blue-ultraviolet regions. Consequently, varying techniques have been devised to create different nanostructures of ZnO. Here, the single step synthesis of ZnO nanostructures was performed on Si(100) substrates with a thin ZnO seed-layer. A modified chemical vapor deposition (CVD) method was developed to accomplish the structure formation. Sb doping of the structures in the gas phase was performed to study its effects on structure and optoelectronic properties. Different structures were realized including nanofilaments, nanoparticles, microflowers, nanorods, nanotubes, and nanocolumns. Only nanorods/columns, and nanotubes are shown in this work. Morphology was examined using scanning electron microscopy (SEM). Energy-dispersive X-ray spectroscopy (EDS) and X-ray powder diffraction (XRD) were used for structural studies. Optoelectronic properties were explored using room-temperature photoluminescence (PL) spectroscopy. PL data show the relative decrease in the number of defects and increase in crystal quality upon increasing reaction time. Significant structural effects were also observed upon doping. Some structural defects might be attributed to the diffusion of Sb ions into the lattices of ZnO, replacement of Zn by Sb, and ionic radii difference. These stacking faults are most likely the reason behind the dominance and broadening of DLE peak.